2011
DOI: 10.1371/journal.pcbi.1002131
|View full text |Cite
|
Sign up to set email alerts
|

Binding Free Energy Landscape of Domain-Peptide Interactions

Abstract: Peptide recognition domains (PRDs) are ubiquitous protein domains which mediate large numbers of protein interactions in the cell. How these PRDs are able to recognize peptide sequences in a rapid and specific manner is incompletely understood. We explore the peptide binding process of PDZ domains, a large PRD family, from an equilibrium perspective using an all-atom Monte Carlo (MC) approach. Our focus is two different PDZ domains representing two major PDZ classes, I and II. For both domains, a binding free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 64 publications
(81 reference statements)
1
25
0
Order By: Relevance
“…Kortemme and co-workers demonstrated that structure-based modeling can predict peptide sequence features recognized by individual PDZ domains in good agreement with high-throughput studies [20]. Stanefa and Wallin studied PDZ/peptide binding free energy landscapes using implicit-solvent Monte Carlo simulations, showing qualitative agreement with experiments [21]. Other studies have demonstrated reasonable ability to describe the space of peptide binders using structure-based calculations [22-24] or sequence-based models trained on high-throughput experimental data [11, 25].…”
Section: Introductionmentioning
confidence: 85%
“…Kortemme and co-workers demonstrated that structure-based modeling can predict peptide sequence features recognized by individual PDZ domains in good agreement with high-throughput studies [20]. Stanefa and Wallin studied PDZ/peptide binding free energy landscapes using implicit-solvent Monte Carlo simulations, showing qualitative agreement with experiments [21]. Other studies have demonstrated reasonable ability to describe the space of peptide binders using structure-based calculations [22-24] or sequence-based models trained on high-throughput experimental data [11, 25].…”
Section: Introductionmentioning
confidence: 85%
“…[36]. It is an implicit-solvent model combining an all-atom representation of the protein chain with an effective energy function taking into account the major contributions of protein interactions, hydrogen bonding, electrostatic attraction, and the hydrophobic effect [40].…”
Section: Methodsmentioning
confidence: 99%
“…It is an implicit-solvent model combining an all-atom representation of the protein chain with an effective energy function taking into account the major contributions of protein interactions, hydrogen bonding, electrostatic attraction, and the hydrophobic effect [40]. The model was developed and tested based on the folding of small peptides and proteins and thereafter adapted particularly for protein-peptide binding [35], [36]. The potential energy function can be decomposed into five terms,representing excluded-volume interactions, local backbone interactions, hydrogen bonding, sidechain-sidechain interactions, and a backbone desolvation effect, respectively [36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations